Teknik Humor Bahasa pada Pertunjukan Konto GRUP KOMEDIAN東京03 (TOKYO ZERO SAN) - Sekar Ayu Ningrum; Roni Roni; Didik Nurhadi (LP. Ma'arif Janggan Magetan, 2023)
Understanding Japanese humor culture is closely related to understanding Japanese communication culture in order to facilitate the communication process in the era of globalization. In this research, the researcher examines further the humor techniques used in the konto performance of the comedian group 東京03 (Tokyo Zero San) based on Berger's theory of humor techniques in order to understand the humor techniques generally used by Japanese society. In this research, the most data falls into the classification of humor techniques, language indicators of exaggeration and repartee, with 5 data each being obtained, Classification of humor language techniques: allusion, insults, and misunderstanding, each with 3 data, classification of humor techniques: bombast, definition, facetiousness, infantilism, over literalness, puns, and satire with 2 data. And classification of humor techniques, irony, ridicule and sarcasm, each of which only obtained 1 data.